2020
DOI: 10.1242/jeb.233221
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin catabolism in Spodoptera exigua, a lepidopteran insect

Abstract: Several prostaglandins (PGs) and PG-synthesizing enzymes have been identified from insects. PGs mediate cellular and humoral immune responses. However, uncontrolled and prolonged immune responses might have adverse effects on survival. PG catabolism in insects has not been reported. Here, using a transcriptomic analysis, we predicted two PG-degrading enzymes, PG dehydrogenase (SePGDH) and PG reductase (SePGR), in Spodoptera exigua, a lepidopteran insect. SePGDH and SePGR expression levels were upregulated afte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Two PG-degrading enzymes, PG dehydrogenase ( SePGDH ) and PG reductase ( SePGR ), act in S. exigua . [ 30 ]. SePGDH and SePGR expression levels are upregulated after immune challenge.…”
Section: Eicosanoid Biosynthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Two PG-degrading enzymes, PG dehydrogenase ( SePGDH ) and PG reductase ( SePGR ), act in S. exigua . [ 30 ]. SePGDH and SePGR expression levels are upregulated after immune challenge.…”
Section: Eicosanoid Biosynthesismentioning
confidence: 99%
“…Here is the question whether the small G proteins including Rac1 activate the actin-associating factors in the hemocyte spreading. Based on Fascin, a molecular component of PGE 2 signaling pathway in D. melanogaster [52], proteinprotein interactions were predicted using the computer modeling program, STRING (http://version10a.string-db.org), and showed that Fascin interacts with 20 proteins including another Rho family small G protein, Cdc42 [30]. In the binding model, Cdc42 interacts with several actin-associated factors including actin monomer, actin-related proteins (Arp2/3) and profilin.…”
Section: Cell Spreadingmentioning
confidence: 99%
See 2 more Smart Citations
“…In humans, PGs are produced by the serial metabolic cascades of phospholipids cyclooxygenase (COX) and prostaglandin synthases (PGSs) and finally inactivated by 15hydroxyprostaglandin dehydrogenase (PGDH). The synthesis and inactivation pathways of PGs are conserved in mammals but partially missing in other animal groups, such as fish [14] and insects [15,16]. However, little is known regarding the PG synthesis and inactivation pathways of crustaceans.…”
Section: Introductionmentioning
confidence: 99%